High‐Performance Pentacene Organic Thin‐Film Transistor by Using Nd2O3 Gate Dielectric Doped with Nb. Issue 5 (10th January 2018) - Ma, Yuanxiao; Tang, Wing Man; Han, Chuanyu; Lai, Pui To
Abstract : Pentacene organic thin‐film transistors (OTFTs) using high‐k Nd x Nb(1− x ) O gate dielectric with different Nb contents ( x  = 1, 0.950, 0.908, and 0.877) are fabricated. The best OTFT has x  = 0.950, achieving a high carrier mobility of 1.95 cm 2  V −1  s −1, small threshold voltage of −1.57 V, small sub‐threshold swing of 0.13 V dec −1, and small hysteresis of 0.13 V. Atomic force microscopy and X‐ray photoelectron spectroscopy measurements reveal that the Nb doping can suppress the hygroscopicity of Nd oxide to produce a smoother dielectric surface, on which larger pentacene grains are grown to result in higher carrier mobility. The hysteresis of the OTFTs is attributed to donor‐like traps associated with the hydroxide formed in Nd2 O3 after absorbing moisture and also acceptor‐like traps (in the form of oxygen vacancies) induced by Nb incorporation. Abstract : High‐performance pentacene organic thin‐film transistor with high carrier mobility, small threshold voltage, and small sub‐threshold swing can be obtained by adopting hybrid high‐k oxide (NdNbO) as gate‐dielectric material, where Nd and Nb complement each other: Nb suppresses the moisture absorption of NdO while Nd helps passivate the defects like oxygen vacancies in NbO.